Dissecting Low Atmospheric Pressure Stress: Transcriptome Responses to the Components of Hypobaria in Arabidopsis - Zhou, Mingqi; Callaham, Jordan B.; Reyes, Matthew; Stasiak, Michael; Riva, Alberto; Zupanska, Agata K.; Dixon, Mike A.; Paul, Anna-Lisa; Ferl, Robert J. (Frontiers in Plant Science, 2017)
Controlled hypobaria presents biology with an environment that is never encountered in terrestrial ecology, yet the apparent components of hypobaria are stresses typical of terrestrial ecosystems. High altitude, for example, presents terrestrial hypobaria always with hypoxia as a component stress, since the relative partial pressure of O2 is constant in the atmosphere. Laboratory-controlled hypobaria, however, allows the dissection of pressure effects away from the effects typically associated with altitude, in particular hypoxia, as the partial pressure of O2 can be varied. In this study, whole transcriptomes of plants grown in ambient (97 kPa/pO2=21 kPa) atmospheric conditions were compared to those of plants transferred to five different atmospheres of varying pressure and oxygen composition for 24 hours: 50 kPa/pO2=10 kPa, 25 kPa/pO2=5 kPa, 50 kPa/pO2=21 kPa, 25 kPa/pO2=21 kPa, or 97 kPa/pO2=5 kPa. The plants exposed to these environments were 10 day old Arabidopsis seedlings grown vertically on hydrated nutrient plates. In addition, 5 day old plants were also exposed for 24 hrs to the 50 kPa and ambient environments to evaluate age-dependent responses. The gene expression profiles from roots and shoots showed that the hypobaric response contained more complex gene regulation than simple hypoxia, and that adding back oxygen to normoxic conditions did not completely alleviate gene expression changes in hypobaric responses.